MENGENALKAN HURUF HIJAIYAH MENGGUNAKAN POSTER HURUF DI TPQ AL-AMIIN DESA ADEAN KECAMATAN BANGGAI TENGAHKABUPATEN BANGGAI LAUT - P Lamadang, Karmila; Riski Nurfadilah; Asrianti S. Muhsin; Asina; Nurianti; Trivivi Julianti (Kreasi: Jurnal Pengabdian Masyarakat, 2022)
Introducing hijaiyah letters to students at TPQ (Qur'an Recitation Park) Al-Amin Adean village with approximately 30 students divided into 2 classes is seen as very effective because it uses attractive Hijaiyah posters. This activity has never been done by asatidz or chasing teachers before. So with the learning through this poster is very effective and it seems that students are very enthusiastic in answering every question asked by the mentors.